Use of Standard and Model based on BOK to Evaluate Professional and Occupational Profiles - Quezada Sarmiento, P. (2015)
Bodies of Knowledge (BOK), contain the relevant information for an area of knowledge, and it is necessary for the development of the science and application in the professional and occupational profiles and the possible incidence in the industry. This paper showed an evaluation of professional and occupational profiles based on standard Software Engineering Body of Knowledge (SWEBOK) and ontological model in order to obtain the necessary information to establish the relationship in these contexts.